An Efficient One-Pot Synthesis of 1-Aminophosphonates - Kaboudin, Babak; Faghih, Samaneh; Alavi, Sajedeh; Naimi-Jamal, Mohammad Reza; Fattahi, Alireza (Synthesis, 2022)
1-Aminophosphonates are valuable compounds with wide range of applications in biological and industry. Various reaction conditions and catalysts have been reported for the synthesis of 1-aminophosphonates via three-component (dialkyl phosphite + aldehyde + amine) or two-component reaction (dialkyl phosphite + imine). Here a solvent-free synthesis of 1-aminophosphonates under very mild reaction conditions is reported. The three-component condensation reactions of dialkyl phosphite, carbonyl compound, and an amine gave 1-aminophosphonates in good to excellent yields under solvent- and catalyst-free conditions at ambient temperature. Hydrophosphorylation of imines in the presence of dialkyl phosphite under the same conditions gave also 1-aminophosphonates in good to excellent yields. These results showed that the reaction needs no catalyst or solvent for activation. It seems a tautomeric form of dialkyl phosphite (as one of the components) catalyzed the reaction. The reaction yield decreased using any solvent. In addition, a novel method is reported for the synthesis of N-deprotected 1-aminophosphonates (analogues of 1-amino acids) from N-PMP 1-aminophosphonate in the presence of TCCA. To understand the activity of the dialkyl phosphite under solvent-free conditions, the DFT calculations have provided insight into the basis of this activity.
Keywords: aminophosphonates; dialkyl phosphite; free aminophosphonates; imine